2021
DOI: 10.3389/fneur.2020.609988
|View full text |Cite
|
Sign up to set email alerts
|

2D Virtual Reality-Based Exercise Improves Spatial Navigation in Institutionalized Non-robust Older Persons: A Preliminary Data Report of a Single-Blind, Randomized, and Controlled Study

Abstract: Background: Spatial navigation is a prodromal dementia marker. Exercise used alongside virtual reality improves many cognitive functions, but effects on spatial navigation are still unclear.Objective: To investigate the effect of virtual reality-based physical exercise with 2D exergames on spatial navigation in institutionalized non-robust older persons.Method: A total of 14 older persons (aged ≧ 60) were randomly allocated to the exergame (EG) and active control (ACG) groups. EG performed exercises with 2D ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, VR-based exposure therapy has been used for eating disorders [ 53 ] and combat-related posttraumatic stress disorders [ 52 ]. For older people, VR-based therapies integrated with movement therapy have been found to improve spatial navigation [ 54 ]. Furthermore, some studies have applied game elements to VR-based rehabilitation such as serious games and virtual spatial wayfinding games [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, VR-based exposure therapy has been used for eating disorders [ 53 ] and combat-related posttraumatic stress disorders [ 52 ]. For older people, VR-based therapies integrated with movement therapy have been found to improve spatial navigation [ 54 ]. Furthermore, some studies have applied game elements to VR-based rehabilitation such as serious games and virtual spatial wayfinding games [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time that exercise has been shown to improve spatial navigation in a healthy adult population using a virtual maze task. A recent pilot study in 14 older adults (aged ≥ 60) found that 2 months of exergaming significantly improved spatial navigation as assessed by the immediate course performance maze time in the Floor Maze Test, a task of exocentric and allocentric navigation (Oliveira et al, 2020 ). Previous reports have also found cross-sectional evidence in adolescents that enhanced cardiorespiratory fitness levels are associated with increased hippocampal volume, which was subsequently associated with spatial learning on a Virtual Water Morris Maze (Herting and Nagel, 2012 ; Prathap et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial navigation and internal representations of the body in space were shown to be impaired in PPPD patients, measured by the virtual version of the Morris water maze test [74]. Improving organisation and orientation through virtual reality appears as a promising treatment target and has been tested in other conditions such as early dementia [75]. Evidence is still limited, but virtual reality interventions are likely to grow in importance and offer insights both into the nature and pathophysiology of PPPD [76].…”
Section: Virtual Realitymentioning
confidence: 99%